2001
DOI: 10.1001/archinte.161.10.1336
|View full text |Cite
|
Sign up to set email alerts
|

Use of Curanderismo in a Public Health Care System

Abstract: Many Hispanic patients who receive their health care at a public hospital system use the services of curanderos. This potentially has important implications for their health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 18 publications
1
44
1
Order By: Relevance
“…One was a brief reflection of a conversation with a curandera (Amerson, 2008), a second identified the "nurse curandera" (Luna, 2003), a third explored the relationship between the curandera and a local Department of Health (Ortiz, 2005), and the last noted the curandero's role within Mexican-Americans' curanderismo practices (Tafur et al, 2009). Of the other five articles, three focused on Hispanic use of traditional medicine, briefly noting the role of a curandero (DeBellonia et al, 2008;Feldmann et al, 2008;Lopez, 2005); one evaluated the rate of use of curanderismo with data collected outside the search limits for this article (Padilla et al, 2001); and the last was a brief photo essay of curanderismo, which noted the role of the curandero (Trotter, 2001). This article differs from the four articles using the term "curanderos" in two primary ways: (a) it offers insights into why Hispanics seek a curandero and (b) it expresses how Hispanics utilize a curandero to treat their health care needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One was a brief reflection of a conversation with a curandera (Amerson, 2008), a second identified the "nurse curandera" (Luna, 2003), a third explored the relationship between the curandera and a local Department of Health (Ortiz, 2005), and the last noted the curandero's role within Mexican-Americans' curanderismo practices (Tafur et al, 2009). Of the other five articles, three focused on Hispanic use of traditional medicine, briefly noting the role of a curandero (DeBellonia et al, 2008;Feldmann et al, 2008;Lopez, 2005); one evaluated the rate of use of curanderismo with data collected outside the search limits for this article (Padilla et al, 2001); and the last was a brief photo essay of curanderismo, which noted the role of the curandero (Trotter, 2001). This article differs from the four articles using the term "curanderos" in two primary ways: (a) it offers insights into why Hispanics seek a curandero and (b) it expresses how Hispanics utilize a curandero to treat their health care needs.…”
Section: Resultsmentioning
confidence: 99%
“…Immigrants believe that traditional providers help them maintain their identity as they become acculturated to their new land (Davis et al, 2011). On the contrary, Padilla et al (2001) found that "assimilation," or the time spent living in the United States, was not a significant indicator of Hispanic use of a curandero.…”
Section: Hispanics Seeking a Curanderomentioning
confidence: 98%
“…There is, however, variation in the literature regarding the use of Hispanic folk medicine in smaller-scale studies. Studies conducted in Colorado and Texas revealed prevalent use of folk medicine among Hispanics (40.7% 24 and 22.0%, 25 respectively). Regional and ethnic differences among the Hispanics in these studies could explain the discrepancy in folk medicine use, and future studies comparing foreign Hispanics of other ethnic backgrounds may be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This lecture was chosen to lead off the classes because it was expected to stimulate discussions that would reveal cultural differences in medical practices of our different ethnic groups. The literature suggests that Mexican Americans interweave alternative and standard medical practices (Gomez-Beloz & Chavez, 2001;Hunt, Arar, & Akana, 2000;Padilla, Gomez, Biggerstaff, & Mehler, 2001;Palinkas & Kabongo, 2000), and we expected to learn of some of them. In this locality, medicinal herbs and other alternative medicine forms are readily available in stores frequented by Hispanics, and this topic was expected to help form the pattern of participant interaction.…”
Section: Developing Health Topicsmentioning
confidence: 99%